Students Collaborative Learning: Micro (Peer) – Teaching in A Classroom - Erny Selfina Nggala Hambandima; Eka Merdekawati Imelda Seseli (Institut Agama Islam Negeri Palopo, 2025)
This study aims to facilitate students to learn and work together in teams, mutual contribution of thoughts, and responsibility for the achievement of learning outcomes as a group or individually, encouraging students to improve learning achievement. Students can have a deeper understanding, develop leadership skills, increase a positive attitude, and increase student self-confidence. The research will be conducted in the Micro-Teaching class, namely in the reteaching cycle, where students will be divided into groups of 3 people to work together in a collaborative learning process to achieve the goals of the re-teaching process. Students can present new or previously learned content using new methods or approaches. The research data was collected through observation and interview methods. Analysis was carried out through analytical descriptive methods and qualitative content analysis, which were then presented formally and informally. The research on this topic is very important to get an idea of good cooperation in breaking permanent learning standards into more flexible learning targets. the divisions of students into groups allow learning instructions to be more in line with the needs of students to provide feedback. In particular, collaborative learning can help students achieve the target of learning objectives in class. A more comprehensive study through this research will also provide information or contributions to the learning process for students and teachers in the teaching and learning process in class.